Museum of Nonhumanity - Gustafsson, Laura; Haapoja, Terike (Punctum Books, 2019)
Museum of Nonhumanity is the catalogue for a full-size touring museum that presents the history of the distinction between humans and animals, and the way that this artificial boundary has been used to oppress human and nonhuman beings over long historical periods. Throughout history, declaring a group to be nonhuman or subhuman has been an effective tool for justifying slavery, oppression, medical experimentation, genocide, and other forms of violence against those deemed “other.” Conversely, differentiating humans from other species has paved the way for the abuse of natural resources and other animals. Museum of Nonhumanity approaches animalization as a nexus that connects xenophobia, sexism, racism, transphobia, and the abuse of nature and other animals. The touring museum hosts lecture programs in which local civil rights and animal rights organizations, academics, artists, and activists propose paths to a more inclusive society through intersectional approaches. The museum also hosts a pop-up book shop and a vegan café. As a temporary, utopian institution, Museum of Nonhumanity stands as a monument to the call to make animalization history.